The Effect of Staphylococcus Aureus on the Electrochemical Behavior of Porous Ti-6al-4v Alloy - Azocar-Guzman, M; Azocar-Guzman, M; Muñoz-Moena, L; Muñoz-Moena, L; Walter, M; Walter, M (Elsevier B.V., 2020)
Ti-6Al-4V alloy has been widely investigated for biomedical applications due to its low density, high specific strength, and favorable corrosion resistance. However, some reported failures have imposed a challenge to improve bone regeneration and fixation, as well as antibacterial properties. A further opportunity for solving this problem is the introduction of porosity. However, this can induce metallic release and corrosion product formation. In this work, a Ti-6Al-4V alloy was exposed to Hank s solution, sterilized and inoculated with Staphylococcus aureus at 37 °C. Surface analysis was carried out by SEM-EDS and XPS. Electrochemical measurements were also performed using chronopotentiometry at open circuit potential, polarization curves, and electrochemical impedance spectroscopy. After exposure, FE-SEM showed some colonies of S. aureus on the sample with 22% porosity. However, XPS analysis revealed that the presence of bacterium influenced the composition of the oxide layer, even more drastically with the increase in added porosity. Moreover, the impedance analysis showed De Levie s behavior, revealing a reduction of pore resistance and modulus of the impedance in the low frequency range in inoculated medium, and polarization curves showed that the passivity potential range was decreased, whereas the passivity current increased in the presence of the S. aureus. © 2020